2021
DOI: 10.1089/rej.2019.2291
|View full text |Cite
|
Sign up to set email alerts
|

Are Japanese Older Adults Rejuvenating? Changes in Health-Related Measures Among Older Community Dwellers in the Last Decade

Abstract: During the last three decades, Japan has become one of the world's top countries for longevity, and the increase in average life expectancy is accompanied by a sharp rise in older population 65 years of age and above to *28%. This study aimed to examine the changes in major health-related measures, including a physical constitution, physical function, and functional capacity of community-dwelling Japanese older people in the last decade. From the data of 13 longitudinal cohort studies on aging conducted in Jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 35 publications
3
36
0
Order By: Relevance
“…Such change in mortality can be interpreted as a shift of age back in the exponential function by the same number of years in all age groups, or as a formal "rejuvenation" occurring in all age groups equally. Indeed, a recent study found that the functional status and aging biomarkers of older Japanese residents in 2017 were consistent with those of younger ages (compared with the biomarkers measured ten years ago for people of the same age) [11]. A similar result was obtained by examining the functional status of Europeans.…”
Section: Age Related and Historical Dynamics Of Mortalitysupporting
confidence: 52%
“…Such change in mortality can be interpreted as a shift of age back in the exponential function by the same number of years in all age groups, or as a formal "rejuvenation" occurring in all age groups equally. Indeed, a recent study found that the functional status and aging biomarkers of older Japanese residents in 2017 were consistent with those of younger ages (compared with the biomarkers measured ten years ago for people of the same age) [11]. A similar result was obtained by examining the functional status of Europeans.…”
Section: Age Related and Historical Dynamics Of Mortalitysupporting
confidence: 52%
“…The percentage of people who had certified care or support needs during the follow-up period was low, at most a little above 20%. A recent study has mentioned the phenomenon of “rejuvenation” among the new generation of Japanese older adults [ 38 ]. To estimate differences in lifelong LTC costs, future studies should use a longer follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…The observation made in the current study that older patients are more likely to be asymptomatic might be unique to Japan. Japan is known as one of the world's top countries for longevity, especially in females [21]. Such prolonged life expectancy has been accompanied by concomitant improvement in overall health and physical functions in the older population, reducing the mortality rate in Japanese female centenarians even further in the last decade [21,22].…”
Section: Discussionmentioning
confidence: 99%